2022
DOI: 10.21037/tcr-22-1607
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab treatment of invasive breast ductal carcinoma induces severe edema: a case report

Abstract: Background: Trastuzumab, a monoclonal antibody which binds to the extracellular domain of HER2, is the first biological drug approved for the treatment of human epidermal growth factor receptor 2 (HER2)positive breast cancer. However, trastuzumab exhibits a series of clinical adverse effects, including cardiac toxicity, nerve damage, abnormal liver function, thrombocytopenia, etc.Case Description: We report a case of a 46-year-old female patient with invasive breast ductal carcinoma (classified as Stage 2B) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…BBB permeability was seen in AD patients in clinical studies using dynamic contrast-enhanced magnetic resonance imaging (MRI) (Starr et al, 2009). Metformin has been shown to protect endothelial cell tight junction, prevent damage to the BBB through the activation of AMPK and inhibition of NF-κB (Zhao et al, 2016). In another study, Takata et al (Ismail Hassan et al, 2020) also found that metformin upregulates the expression of ZO-1, occludin, and claudin-5 in brain microvascular endothelial cells via AMPK activation.…”
Section: Cell and Animal Experimentsmentioning
confidence: 99%
“…BBB permeability was seen in AD patients in clinical studies using dynamic contrast-enhanced magnetic resonance imaging (MRI) (Starr et al, 2009). Metformin has been shown to protect endothelial cell tight junction, prevent damage to the BBB through the activation of AMPK and inhibition of NF-κB (Zhao et al, 2016). In another study, Takata et al (Ismail Hassan et al, 2020) also found that metformin upregulates the expression of ZO-1, occludin, and claudin-5 in brain microvascular endothelial cells via AMPK activation.…”
Section: Cell and Animal Experimentsmentioning
confidence: 99%